Gender Inequity in African University Engineering Programs - Fredua-Kwarteng, Eric; Effah, Catherine (International Higher Education, 2017)
African women are grossly underrepresented in undergraduate engineering programs across universities in Africa. This paper reviews policies that some African universities have adopted to address the problem and suggests strategies for greater gender equality.